Electrodetermination of Gallic Acid Using Multi-Walled Carbon Nanotube Paste Electrodes and N-Octylpyridinium Hexafluorophosphate - Aguirre-Quintana, M; Aguirre-Quintana, M (John Wiley and Sons Inc, 2022)
In this work, the determination of gallic acid was performed using surface-renewable carbon paste electrodes fabricated with multi-walled carbon nanotubes (MWCNT) and a mixture of N-octylpyridinium hexafluorophosphate (OPyPF6) ionic liquid with mineral oil (MO) as binder. This system shows remarkable amperometric sensor characteristics and promotes a better electronic transfer. An electroanalytical study of gallic acid shows a linear range from 4.98±0.25 to 74.1±2.2 μmol L−1, with R2=0.9958 and an experiment a limit of detection of 2.70±0.08 μmol L−1 (S/N=3), and a sensitivity of 0.029 μA μmol−1 L. © 2022 Wiley-VCH GmbH.